Role of initial and follow-up lactate dehydrogenase titer in coronavirus disease 2019 pneumonia: A single-center experience - Shital Patil; Deepak Patil; Shubhangi Khule (Wolters Kluwer Medknow Publications, 2023)
Aims: Robust data of lactate dehydrogenase (LDH) are available as a prognostic marker in hematology, malignancy, and pneumocystis pneumonia, and we have analyzed its usefulness in coronavirus disease 2019 (COVID-19) pneumonia. Materials and Methods: A prospective, observational, follow-up study included 1000 COVID-19 cases confirmed with real-time reverse transcription polymerase chain reaction. All cases were assessed with lung involvement documented and categorized on high-resolution computerized tomography (CT) thorax, oxygen saturation, inflammatory marker as LDH at entry point, and follow-up. Age, gender, comorbidity, and use bilevel-positive airway pressure/noninvasive ventilation (BIPAP/NIV) and outcome as with or without lung fibrosis as per CT severity were key observations. Statistical analysis is done by using Chi-square test. Results: In a study of 1000 COVID-19 pneumonia cases, age (<50 and >50 years) and gender (male versus female) have a significant association with LDH in predicting severity of COVID-19 pneumonia (P < 0.00001 and P < 0.010, respectively). CT severity score at entry point with LDH level has a significant association (P < 0.00001). LDH level has a significant association with duration of illness (P < 0.00001). Comorbidities such as diabetes mellitus, hypertension, chronic obstructive pulmonary disease, ischemic heart disease, and obesity have a significant association with LDH level (P < 0.00001). LDH level has a significant association with oxygen saturation (P < 0.00001). BIPAP/NIV requirement during course of hospitalization has a significant association with LDH level (P < 0.00001). Timing of BIPAP/NIV requirement in critical care setting has a significant association with LDH level (P < 0.00001). Follow-up LDH titer during hospitalization as compared to entry point abnormal LDH has a significant association in post-COVID lung fibrosis (P < 0.00001). Follow-up LDH titer during hospitalization as compared to entry point normal LDH has a significant association in post-COVID lung fibrosis (P < 0.00001). Conclusions: LDH has documented a very crucial role in COVID-19 pneumonia in predicting severity of illness, progression of illness, and sequential LDH titers, which will help assess response to treatment during hospitalization and analyze post-COVID lung fibrosis.